2011
DOI: 10.1007/s10008-011-1489-2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of loading and particle size on the oxygen reaction in CGO impregnated Pt electrodes

Abstract: Porous platinum electrodes impregnated with Gd x Ce 1−x O 2−δ (CGO) are investigated to characterise how nano-sized CGO grains affect the oxygen reaction. Impedance measurements were performed at temperatures between 450 and 750°C and at oxygen partial pressures of 0.2 and 5×10 −5 bar for electrodes with various CGO loadings and electrodes annealed at various temperatures. The morphology was characterised by scanning electron microscopy and the CGO grain size was determined from X-ray diffraction peak broadeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…6,[8][9][10] In a similar case, infiltration of gadolinia doped ceria (GDC) into porous Pt skeleton to enhance electrode performance has recently been reported. 22 It was shown that GDC infiltration improved the electrode performance significantly (from 3.9 Ohm.cm 2 to 0.7 Ohm.cm 2 per electrode at 700 • C). However, the mixed conductivity of GDC and the fact that it exhibits some catalytic activity for the oxygen reduction reaction needs to be considered for a comparison with the present work.…”
Section: Resultsmentioning
confidence: 95%
“…6,[8][9][10] In a similar case, infiltration of gadolinia doped ceria (GDC) into porous Pt skeleton to enhance electrode performance has recently been reported. 22 It was shown that GDC infiltration improved the electrode performance significantly (from 3.9 Ohm.cm 2 to 0.7 Ohm.cm 2 per electrode at 700 • C). However, the mixed conductivity of GDC and the fact that it exhibits some catalytic activity for the oxygen reduction reaction needs to be considered for a comparison with the present work.…”
Section: Resultsmentioning
confidence: 95%
“…By tuning the infiltration step or the concentration of the precursor, particles can either be deposited discretely or in a connected network. Another catalytic material doped ceria (XDC, X=Metal), attracted attention due to its flexibility of use either in the anode or cathode or even the electrolyte material [30,32,37,42,44,45,51,53,58,59,61,63,64,69,72,76,77,80,83,87,91,96,99,100,102,103,105,107,109,113,121,122,130,134,140,147] . For example, gadolinium-doped ceria (GDC) acts as an ionic conductor, and also by switching the valence character of ceria from +4 to +3 repeatedly, nanoparticles can achieve hydrogen storage capability.…”
Section: Electrochemical Performance Enhancement By Catalyst Infiltramentioning
confidence: 99%